1982
DOI: 10.1128/aac.22.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of functional lymphocyte subpopulations by ribavirin

Abstract: The present studies were designed to examine the effects of ribavirin (1-beta-D-ribofuranosyl-1,2,4-triazole-3-carboxamide), a broad-spectrum antiviral agent, on the generation of murine antibody responses in vitro. Whereas primary and secondary sheep erythrocyte-specific, plaque-forming cell responses by normal murine spleen cells were enhanced by low concentrations of ribavirin (1 microgram per culture), they were strongly inhibited by higher concentrations of ribavirin (5 to 10 micrograms per culture). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Similar observations have been made during influenza virus infection, where ribavirin improved survival rate and lung pathology without reducing viremia in the lungs 36 . The potential mechanisms leading to the observed cell protective effect remain unresolved, but possible explanations include ribavirin’s modulation of immunological and pathophysiological pathways 37 , 38 , thereby inhibiting macrophage activation and cytokine production 37 ; and the anti-proliferative effect on lymphocytes observed at high concentrations of ribavirin 39 . The discrepancy between ribavirin’s antiviral efficacy observed in vitro 7 and its main mechanism of action in vivo could be due to different factors, including the type of cells infected and the actual pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been made during influenza virus infection, where ribavirin improved survival rate and lung pathology without reducing viremia in the lungs 36 . The potential mechanisms leading to the observed cell protective effect remain unresolved, but possible explanations include ribavirin’s modulation of immunological and pathophysiological pathways 37 , 38 , thereby inhibiting macrophage activation and cytokine production 37 ; and the anti-proliferative effect on lymphocytes observed at high concentrations of ribavirin 39 . The discrepancy between ribavirin’s antiviral efficacy observed in vitro 7 and its main mechanism of action in vivo could be due to different factors, including the type of cells infected and the actual pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in two separate cases, one in Thailand, and one in the United States, ribavirin was administered, again demonstrating a lack of efficacy [46,48]. It is hypothesized that this disappointing performance of ribavirin is due to its interference with the Th1/Th2 immune response, thus hindering production of effective antibodies that are essential for RABV clearance [49].…”
Section: Current Treatment Of Rabv Infectionmentioning
confidence: 99%
“…In in vitro assays using nonreplicating agents, ribavirin has been shown to inhibit the development of antibody responses. 34 In a study of infants receiving either no therapy, a placebo, or ribavirin for bronchiolitis, it was demonstrated that both RSV-specific IgA and IgE antibody responses were inhibited in the ribavirin-treated group 35 (Table 5). In addition, purine nucleosides and nucleotides may modulate mast cell secretion, and it has been demonstrated that ribavirin inhibits the release of preformed granules similar to histamine as well as reducing synthesis of LTs from murine mast cells.…”
Section: Therapeutic Approachesmentioning
confidence: 99%